Nickel-Catalyzed Intramolecular Nucleophilic Addition of Aryl Halides to Aryl Ketones for the Synthesis of Benzofuran Derivatives - Zhu, Xiao-Rui; Deng, Chen-Liang (Synthesis, 2021)
A nickel-catalyzed intramolecular nucleophilic addition reaction of aryl halides to aryl ketones for the formation of benzofuran derivatives has been developed. A number of substrates bearing electron-donating or electron-withdrawing groups were subjected to the standard reaction conditions, giving the corresponding products in moderate to good yields.
Keywords: nickel; zinc powder; intramolecular addition; cyclization; benzofuran